Cyclic experiments on screwed connections for corrugated steel sheathed CFS shear walls - Yan, Zhao; Wenying, Zhang; Xiuli, Du; Shaole, Yu; Cheng, Yu (Journal of constructional steel research, 2025)
This study investigates the hysteretic load-displacement behavior of screwed connections in cold-formed steel (CFS) shear walls sheathed with corrugated steel sheathing (CSS) under cyclic loading. The screwed connection performance of corrugated steel sheathed CFS shear walls is governed by a combination of shear and tensile forces, with a particular focus on the hysteretic response perpendicular to the corrugations in this research. The test results revealed that under negative loading, the peak load of specimens increased with sheathing thickness but decreased with higher corrugation rib. Specimens exhibited slight variations in peak load under positive loading, while substantial stiffness differences were observed among those with different sheathing thicknesses and types. Screw spacing and loading method demonstrated negligible influence on hysteretic responses. Additionally, a constitutive hysteresis model was developed based on experimental data for refined numerical simulations of corrugated steel sheathed shear walls. The work is intended to provide critical missing information for the design of framed shear walls with CSS in multi-storey buildings. •The cyclic experiments on screwed connections for corrugated steel sheathed CFS shear walls were investigated.•Further exploration was conducted into the nonlinear behavior of the screwed connections perpendicular to the corrugations.•A hysteretic constitutive model for the CFS-to-CSS screwed connection was established using Pinching4 material model.